2020
DOI: 10.1177/1055665619898596
|View full text |Cite
|
Sign up to set email alerts
|

Achieving Consensus in the Measurement of Psychological Adjustment to Cleft Lip and/or Palate at Age 8+ Years

Abstract: Background: Consensus regarding optimal outcome measurement has been identified as one of the most important, yet most challenging developments for the future of cleft lip and/or palate (CL/P) services. In 2011, a process began to adopt a shared conceptual framework and to identify a set of core outcome measures for the comprehensive assessment of psychological adjustment. Objectives: The aim of the current article is to outline the collaborative process used to achieve consensus in the academic and clinical m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 32 publications
0
19
0
Order By: Relevance
“…Clinicians will have to consider the strengths and limitations in relation to both questionnaires as well as the resources of the hospital system when choosing to implement either PROM. Collaboration between clinicians and researchers has earlier been suggested for implementation of PROMs with both “face validity and scientific rigor” ( Stock et al, 2020 ). Both PROMs have the potential to allow CL/P teams to enhance patient–clinician communication ( Wormald & Rodrigues, 2018 ) and shared decision-making between patients and clinicians ( Dobbs et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Clinicians will have to consider the strengths and limitations in relation to both questionnaires as well as the resources of the hospital system when choosing to implement either PROM. Collaboration between clinicians and researchers has earlier been suggested for implementation of PROMs with both “face validity and scientific rigor” ( Stock et al, 2020 ). Both PROMs have the potential to allow CL/P teams to enhance patient–clinician communication ( Wormald & Rodrigues, 2018 ) and shared decision-making between patients and clinicians ( Dobbs et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, they would have to be used in combination to represent a holistic assessment of HRQOL in patients with CL/P. A list of proposed PROMs for research and clinical work regarding psychological adjustment, as well as satisfaction with appearance, can be found in a publication by Stock et al (2020) . This work was published for the Global Task Force for Holistic Outcomes, an initiative of the American Cleft Palate-Craniofacial Association.…”
Section: Methodological Issues With Proms In Cl/p Related Health Care and Researchmentioning
confidence: 99%
“…A team of physicians and experts, utilizing a coordinated approach as noted in Table 3 , is essential to care for children who have CLP [ 16 ]. Longitudinal studies have looked at psychological adjustment to CLP to determine clinical utility [ 17 ]. In addition, prenatal diagnosis facilitates timely counseling of the parents by the CLP team and increases preparedness for the family which improves the child’s quality of treatment enabling a quality and standard of life as close to the norm as possible [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…We read with interest this issue’s article by ( Stock et al, 2020 ), which reviewed patient-reported measures for psychological adjustment to cleft lip and/or palate in people aged 8 years or older. The authors aimed to appraise available measures, before recommending a core set, presumably for use in both research and clinical practice.…”
Section: Dear Editormentioning
confidence: 99%